MICROBIOLOGICAL AND PHYSICOCHEMICAL ANALYSIS OF HOMEMADE FRESH MILK MARKETED IN ANÁPOLIS - GO (CIPEEX, 2025)
Title:Microbiological and Physicochemical Analysis of Homemade Fresh Milk Marketed in Anápolis - GOObjective:To analyze the microbiological and physicochemical quality of homemade fresh milk sold in the Anápolis - GO region, focusing on the detection of Salmonella spp.Justification:Raw milk consumption is common in family and rural settings, often without proper sanitary inspection, posing a public health risk due to potential contamination with pathogenic microorganisms.Methodology:Sampling: Milk samples collected over one year.Physicochemical analyses: pH, titratable acidity, density, fat content, protein content, cryoscopy, and water activity.Microbiological analyses: Mesophilic bacteria count, total and thermotolerant coliforms, molds and yeasts, and detection of Salmonella spp. using selective media and confirmatory tests.Methodological references: AOAC, Embrapa, MAPA, and ANVISA.Data comparison: Results will be compared with MAPA Normative Instruction No. 76/2018 and ANVISA Normative Instruction No. 161/2022.Expected Results:Variations in physicochemical parameters among samples.Presence of Salmonella spp. in some samples.Evidence of deficiencies in milking and milk preservation practices.Impact and Applications:The findings may support educational initiatives and hygienic-sanitary control strategies, promoting safer artisanal milk production and consumption.